Suitabilty Analysis of Polychaeta Habitat in Seagrass Ecosystem, Parang Island, Karimunjawa, Central Java - Ibadur Rahman (AQUASAINS, 2016)
Polychaeta is one of many organisms associated to seagrass bed. To grow optimally, polychaeta needs habitat that suitable to its habit and feeding behaviour. This research aims to analyze polychaetahabitat suitability on seagrass ecosystem at Parang Island, Karimunjawa. The research was held on September 2012, at Parang Island, Karimunjawa. The result shows that the seagrass bed is a mixed community type consisted of 7 seagrass species, and 12 kindsof polychaeta which Spionidae is the highest in abundance (141 ind.m-2). The result of Principal Component Analysis (PCA) indicates that polychaeta abundance was aﬀected by some factors, i.e; organic material of substrate, graveled and muddy substrate, dissolved oxygen, depth, nitrate concentration, zooplankton, and seagrass percent  cover.